(untitled) (Revista da Faculdade de Odontologia - UPF, 2017)
Objective: to critically assess in vitro methods used to evaluate the mechanical behavior of endodontically treated teeth restored with intra-radicular posts and cores. Literature review: a literature search of in vitro studies was conducted in PubMed database using the search terms (“endodontic*” OR “intracanal post”) AND (“fracture” OR “resistance” OR “load” OR “strength”). A filter for publication date was set to return studies from the last five years (from October 2010 to October 2015). The research strategy resulted in 1,556 studies. After the analysis of the eligibility criteria, 92 articles were included in a descriptive analysis. Human upper central incisors were used most frequently. The natural mobility of teeth was simulated using an artificial periodontal ligament in 66.7% of the studies. In 32.2% of the studies, the load to fracture was applied directly to the core. Thermocycling was performed in 27.2% of the studies. Cyclic loading was used in 38% of the studies. Final considerations: periodontal ligament simulation, thermocycling and cyclic loads are some methods that have been employed to approximate laboratory studies to the clinical conditions that teeth restored intra-radicular posts and cores are submitted. Novel test methodologies, such as step-test and staircase approach, have been used to evaluate the fatigue behavior of this systems. However, it is important do highlight that, considering the context in which most of the included studies were performed, the extrapolation of the results to the clinical practice should be made carefully